The Impact of Comorbidity on Survival in Patients With Head and Neck Squamous Cell Carcinoma: A Nationwide Case-Control Study Spanning 35 Years - Ruud Kjær, Eva Kristine; Jensen, Jakob Schmidt; Jakobsen, Kathrine Kronberg; Lelkaitis, Giedrius; Wessel, Irene; von Buchwald, Christian; Grønhøj, Christian (Frontiers in Oncology, 2021)
Background: Comorbidity is presumed to impact survival of head and neck squamous cell cancer (HNSCC) patients. However, the prevalence and prognostic impact of comorbidity in these patients is not yet well established. The aim of this study is to outline the comorbidity burden of HNSCC patients and investigate the relation to overall survival and cancer-specific mortality. Methods: The comorbidity burden of patients registered with HNSCC in the Danish Cancer Registry between 1980-2014 was evaluated based on the Charlson Comorbidity Index (CCI). Patients’ risks of comorbid conditions compared to age- and gender-matched controls were estimated by odds ratios (OR). The impact of comorbidity on overall survival and cancer-specific mortality was evaluated by Cox regression and Kaplan-Meier survival analysis. Results: A total of 25,388 HNSCC patients were included (72.5% male; mean age 63.2 years at diagnosis; median follow-up 3.0 years). CCI at diagnosis was significantly higher in patients compared to controls (p<0.001). The most common comorbid conditions among the patients were additional non-metastatic malignancy (10.9%) and cerebrovascular disease (7.7%). Compared to controls, patients had higher odds of metastatic malignancy (OR: 4.65; 95%CI: 4.21-5.15; p<0.001), mild liver disease (OR: 6.95; 95%CI: 6.42-7.53; p<0.001), and moderate-severe liver disease (OR: 7.28; 95%CI: 6.14-8.65; p<0.001). The multivariate Cox analysis revealed increasing hazard ratios with increasing CCI and in coherence the Kaplan-Meier curves¬¬ showed poorer overall survival and increased cancer-specific mortality in patients with higher CCI. Conclusion: HNSCC patients’ comorbidity burden was significantly greater compared to the general population and increased comorbidity was correlated with increased cancer-related mortality.